Computational study on the effect of temperature in fluidized bed gasifier - Bahrom, Norelyani (2013)
Fluidized bed gasifier which is excellent in temperature control was selected to be modelled in ANSYS FLUENT. Temperature is one of the important hydrodynamic parameter in developing the large-scale industrial power plant. Study will be emphasized on three different temperatures where each of them was expected to give different view on the effect within the gasifier. Results of gases composition were compared with existing experimental data from the pilot scale gasifer in TNBR, Bangi. Distribution of gas and solid phase temperature in the gasifier has been studied by considering the heat generated from each process. Using Eulerian Eulerian approach, different phases of solid and gas is being treated mathematically in computational fluid dynamic (CFD). Chemical reaction for heterogeneous and homogenous is the key for this computational study. For the three case studies, result has shown that the gas temperature was evenly distributed as it reaching up to the gasifier outlet and carbon monoxide (CO) composition is observed to be decreasing to zero quantity as it moves towards the upper part of the gasifier.